Food lipids : chemistry, nutrition, and biotechnology - Akoh, Casimir C., 1955-; Min, David B. (Food science and technology (Academic Press), 2008)
Highlighting the role of dietary fats in foods, human health, and disease, this book emphasizes lipids from the point of entry into the food supply. It covers polyunsaturated lipid oxidation in aqueous systems, total antioxidant evaluation and synergism, and tocopherol stability and prooxidant mechanisms of oxidized tocopherols in lipids.